Tindak Tutur Ekspresif dan Komisif dalam Debat Calon Presiden Republik Indonesia 2024 Pada Youtube Akun Tv One News - Henita, Henita; Kasmantoni, Kasmantoni; Randi, Randi (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This study aims to describe the forms of expressive speech acts and commissive speech acts in the first presidential debate of the 2024 presidential candidates of the Republic of Indonesia, as seen on the TV One News YouTube channel. The method used in this research is qualitative descriptive. The data source for this study is a video from the TV One News YouTube channel, which contains speech acts expressed by the presidential candidates during the first debate, downloaded via YouTube. The data obtained consists of the forms of expressive and commissive speech acts in the first presidential debate of the 2024 presidential candidates on the TV One News YouTube channel. Data collection techniques include observation, note-taking, and documentation, with data analysis involving data reduction, data display, and conclusion drawing or verification. The results of the study show that the forms of expressive speech acts consist of 8 utterances: thanking, apologizing, expressing anger, complaining, criticizing, praising, mocking, and congratulating. Among these 8 forms, 56 instances of expressive speech acts were found. The forms of commissive speech acts consist of 5 utterances: promising, intending, vowing, offering, and swearing. From these 5 forms, 26 instances of commissive speech acts were identified in the debate. In conclusion, there are 8 forms of expressive speech acts, which are thanking, apologizing, congratulating, complaining, praising, expressing anger, mocking, and criticizing, and 5 forms of commissive speech acts, which are promising, intending, vowing, offering, and swearing. Keywords: Expressive, Presidential Debate, Commissive, Speech Acts